Intrauterine growth restriction – part 1. (16th December 2016) - Sharma, Deepak; Shastri, Sweta; Farahbakhsh, Nazanin; Sharma, Pradeep
Abstract: Intrauterine growth restriction (IUGR) is a major and silent cause of various morbidity and mortality for the fetal and neonatal population. It is defined as a rate of fetal growth that is less than normal for the growth potential of that specific infant. The terms IUGR and small for gestational age (SGA) are often used interchangeably, although there exists subtle differences between the two. IUGR/SGA is an end result of various etiologies that includes maternal, placental and fetal factors and recently added genetic factors too, also contribute to IUGR. In this review article we will cover the antenatal aspect of IUGR and management with proven preventive intervention.